Curta-metragem: O Circo Wurdulak - Godoy, Ana Paula; Zeraik, Beatriz Nunes; Vietri, Luísa Souza; Lima, Vitor Antonio de (Universidade Federal de São Carlos, 2023)
Circo Wurdulak is a short film project in 2D full animation and cut-out, lasting 7 minutes, based on the short story of the same name written in 2021, by Vitor Lima, under the pseudonym Zorluke (co-writer of the project). The short film presents a universe in which reality is intertwined with the supernatural, through fantastic horror animation. Based on German expressionism cinema from the 1920s, it follows an aesthetic that uses resources from horror genre cinema to tell the story. The project aims, through narrative, aesthetics, editing and sound accompaniment, to cause strangeness, confusion, fear and horror, attracting an audience that is generally not the focus of most animation productions in Brazil. Therefore, we focus on creating animation for teenagers and young adults.
Short film: The Wurdulak Circus
Keywords: Animação; Terror; 2D; CIENCIAS SOCIAIS APLICADAS::COMUNICACAO